Tathwir Manahij Al-Darama fi Baramij Ta’lim Al-Lughah Al-Arabiya li An-Nathiqiin bi Ghairiha - Khaled Ahmed Mahmud (HuRuf Journal : International Journal of Arabic Applied Linguistic, 2021)
That the planning of the language curriculum in educational programs is very accurate, where the language curriculum focuses on identifying the knowledge and values learned by the learner, in order to achieve the educational outputs aimed at by the designers of the curriculum, and in view of the Arabic language curricula provided to non-Arabic students we find it suffers from a huge lack of development, and is based on the traditional objectives that cause boredom and aversion to the Arabic language, and now we have modern methods based on appropriate perceptions of the nature of the era and the nature of the learners.  Themselves and there is no doubt that drama and its treatment in the linguistic curriculum is attractive for learners, and how to employ drama in Arabic language programs is one of the new forms in the introduction of the language curriculum, the curriculum on how to plan for teaching and learning and measuring educational systems and evaluating them. This study will address the design of dramatic courses, curriculum development, analysis of the needs of students in universities or schools and contextual factors that are seen when planning the language program A large number of students sit in classrooms to master a language, and they make a great effort, and many curriculum designers and teachers spend a lot of time preparing a course, teaching the language in the classroom. In light of this, there are educational principles on which the process of preparing a curriculum, and values that reflect these elements in education, review these processes in cash and study, and the development of the language curriculum needs some processes to develop it, lies in the procedures used in determining the content of the language program, the needs of learners and updating them, contextual factors when stitching a language program, knowledge of general and private objectives, teaching and development and measuring the effectiveness of the language program.أن  تخطيط  المناهج اللغوبة  فى  البرامج  التعليمية  يعد  أمر  دقيق  للغاية  ، حيث تركز المناهج  اللغوية  على  تحديد  المعارف  والقيم  التى  يتعلمها  الدارس  ،من  أجل  تحقيق  النواتج  التعليمية  التى يهدف  إليها  من  قبل المصممين للمناهج  ،وبالنظر  إلى  مناهج اللغة العربية  المقدمة إلى  االطلاب  الناطقين  بغير  العربية نجدها  تعانى  من  نقص  هائل  فى  التطوير  ،وتستند  إلى  الاهداف  التقليدية  التى تسبب  الملل  والنفور  من  اللغة  العربية ،وأصبخ  الآن  من  الضرورى أن  نصمم مناهج  مبنية  على تصورات  عصرية  ملائمة  لطبيعة  العصر وطبيعة  الدارسين  أنفسهم  ولا  شك  أن  الدراما  ومعالجتها فى  المناهج  التعليمية اللغوية أمر جذاب بالنسبة  للدارسين  ،وكيفية  توظيف  الدراما  فى  برامج  اللغة  العربية  يعد من  الأشكال الجديدة  فى  طرح  المناهج اللغوية فالمنهج على كيفية التخطيط للتعليم والتعلم وقياس الأنظمة التعليمية وتقويمها. وهذه الدراسة سوف تتناول  تصميم المقررات الدرامية وتطوير المناهج، وتحليل حاجات الدارسين في الجامعات  أو المدارس والعوامل السياقية التي ينظر إليها عند تخطيط البرنامج اللغوي والمتعلقة بالمجتمع والمؤسسة التعليمية، وأهدافه وأنواعه، وتطويره،  والقضايا التي تختار في تصميم المواد التدريسية وقياس فعالية البرنامج اللغوي المعد عبر تخطيط الغايات ونواتج التعلم. وكذلك  تتناول تصميم المقررات وتخطيط الدورات، وأهمية المواد التدريسية وتصميميها، ثم أخيرا أنواع التقويم المستخدمة،  ستتناول  هذه  الورقة  البحثية  بالوصف والتحليل  الإجراءات التي تستخدم لتحديد محتوى برنامج دراسي لغوي مبنى  على  الدراما، وبيان حاجات الدارسين وتحديدها، ثم العوامل السياقية المتبعة عند تخطيط منهج لغوي، والأهداف العامة والخاصة في التدريب وكيف يمكن تطويرها، والعوامل التي يتضمنها اختيار المواد الدراسية وتكيفها وتصميمها، وأخيرا كيفية قياس فعالية البرنامج اللغوي وذلك  من  خلال رؤية  شاملة   حيث  أشتملت  الورقة البحثة  على  مقدمة  تهئ للتطوير المناهج  اللغوية  ومفهوم  الدراما  التعليمية  ،ثم  يبدأ  الفصل الأول بمفهوم  المنهج  الدرامى  والدراما  التعليمية ،وأصول ومبادئ  تطوير  المنهج اللغوى   وكيفية  تصميم  المنهج  اللغوى  ،ثم  يبدا الفصل  الثانى  بتصور  مقترح  عن  المنهج  الدرامى  للغة  العربية  للناطقين  بغيرها  ، مدخلاته  ومخرجاته  ،وكيفية  إعداد  المنهج  المعتمد  على  نصوص  دراما  ومدعمة  بمرئيات  تساعد  الطلاب على  تنمية مهارات  اللغة  الأربعة ( الاستماع – التحدث -  القراءة  -  الكتابة.